Pengaruh Gaya Kepemimpinan, Komitmen Organisasi Dan Budaya Organisasi Terhadap Kepuasaan Kerja Karyawan PT SOS Indonesia - Neneng Suhartini; Christian Wiradendi Wolor; Marsofyati Marsofyati (Pusat Riset dan Inovasi Nasional, 2024)
The Influence of Leadership Style, Organizational Commitment and Organizational Culture on PT SOS Indonesia Employee Job Satisfaction. Office Administration Education Undergraduate Study Program, Faculty of Economics, Jakarta State University.The aim of this research is to determine the influence of leadership style, organizational commitment and organizational culture on the job satisfaction of PT SOS Indonesia employees. The type of research carried out uses quantitative research methods. The data collection technique used was through a questionnaire which was measured using a Likert scale from a value between one to five with a total of 16 questions. The population in the study was 135 employees of PT SOS Indonesia with a sample size of 100 employees at PT SOS Indonesia. This research uses a non-probability sampling technique with purposive sampling with the Slovin formula with a difficulty level accuracy of 5%. The analysis technique used in this research is SEM PLS (Structural Equation Modeling - Partial Least Squares) which was carried out using SmartPLS 4.0 software. Data The analytical methods used in this research include measurement model analysis, structural model analysis, and direct influence hypothesis testing. The results of data analysis show that the leadership style variable has a positive and significant effect on job satisfaction, the organizational commitment variable has a positive and significant effect on job satisfaction and organizational culture has a positive and significant effect on job satisfaction.